Möbius media: popular culture, folklore, and the folkloresque - Tolbert, Jeffrey A., editor; Foster, Michael Dylan, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2024)
Broadens folklore analysis to critically consider all manner of vernacular and commercial engagements to investigate how "folklore" is understood and mobilized within a variety of popular discourses and in different commercial marketplaces, in commodities, and in genres.--Provided by publisher.
Introduction: the value of recursion / Jeffrey A. Tolbert -- Bits and pieces: exotification and the allusion of authenticity in Southern African wildlife tourism / Lisa Gilman -- Simply Sara and the art of hominess: performing the folkloresque in the YouTube kitchen / Susan Lepselter -- Fairytale as fuck: antimodern media, sensory experience, and the folkloresque / Anthony Bak Buccitelli -- Folkloresque at work: tales of the Nepali theki / Claire Cuccio -- Fictitious folklore and world-making in popular culture / Timothy Gitzen and Ilana Gershon -- Local cosmologies, the folkloresque, and the fantastic in the Japanese Himukaizer tokusatsu action hero media mix / Debra J. Occhi -- Monstrous longings in the age of insurrection: a Twilight postmortem / Kimberly J. Lau -- From Jacob Grimm to the White Witch of Devil's End: Hammer horror, folk horror and the folkloresque in Doctor Who / Paul Cowdell -- "Vernacular wolf-men": the folkloresque transformation of the werewolf in Universal's cycle of werewolf films (1935-1948) / Craig Thomson -- Can such things be? Ambrose Bierce and the newspaper folkloresque / Paul Manning -- The devil you know: reclaiming the ambivalent witch in modern traditional witchcraft craft / Catherine Tosenberger -- Atlantis: unraveling a folkloresque tapestry / David S. Anderson -- Monk, Greeley, Ward, and Twain: the folkloresque of a western legend / Ronald M. James -- Nothing is original: mimesis, Amabie, and the spirit of open access / Michael Dylan Foster.
Keywords: Folklore in popular culture; Folklore -- Economic aspects; Folklore -- Social aspects; Folklore in motion pictures; Folklore in motion pictures; Mass media and folklore